PENGARUH EFFECTIVENESS DAN INTUITIVENESS E-WALLET GOPAY TERHADAP MINAT PENGGUNAAN APLIKASI GOJEK BAGI KALANGAN MAHASISWA - Tarigan, Arihta; Frangoulis, Alfredo (Universitas Multimedia Nusantara, 2023)
Abstract- This study aims to investigate the impact of the effectiveness and intuitiveness of GoPay on the interest in using the Gojek application among university students, particularly those at Bunda Mulia University. Data were collected through an online survey involving a sample of 100 students, selected based on the Slovin formula and representing the total number of students at Bunda Mulia University. The results of the data analysis using multiple linear regression showed that the effectiveness and intuitiveness of GoPay have a significant positive influence on the interest in using the Gojek application. These findings provide a better understanding of the factors influencing the acceptance and usage of the Gojek application among students, serving as a guide for the development of future app-based payment services. Keywords: Effectiveness; E-Wallet; Fintech; Intuitiveness; Interest